1999
DOI: 10.5032/jae.1999.01074
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Values In Agricultural Education

Abstract: This study determined perceptions of agricultural education teachers nationwide as to what values should be taught to students enrolled in high school agriscience courses. The population was secondary agricultural teachers who taught in public secondary schools in the United States during I99 7-98. Most of the teachers were middle-aged, white males who taught agriculture for an average of 14 years. The average school size where these agriculture teachers taught was 750 students, andenrollment in agriculture re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The conclusion that FFA members should receive opportunities to develop communication skills and be involved in leadership development is consistent with Staller (2001), who stated that the FFA component, compared with the instructional component, was best suited to teach life skills. Furthermore, this conclusion is consistent with Lockaby and Vaughn's (1999) finding that of the three components of agricultural education, FFA is the best for teaching values and attitudes to students. These findings imply that the expert panel is in line with the literature, and it is recommended that these quality indicators be embraced by the profession.…”
Section: Discussionsupporting
confidence: 89%
“…The conclusion that FFA members should receive opportunities to develop communication skills and be involved in leadership development is consistent with Staller (2001), who stated that the FFA component, compared with the instructional component, was best suited to teach life skills. Furthermore, this conclusion is consistent with Lockaby and Vaughn's (1999) finding that of the three components of agricultural education, FFA is the best for teaching values and attitudes to students. These findings imply that the expert panel is in line with the literature, and it is recommended that these quality indicators be embraced by the profession.…”
Section: Discussionsupporting
confidence: 89%
“…For example, the Vocational Agriculture Teachers Association of Texas (2009), have impressed the fact that a teacher in the area of agriculture, food, and natural resources must perform many duties to facilitate the success of the career of teaching. Similarly, it was found in a study conducted by Lockaby and Vaughn (1999) in the US, that the Agricultural science teachers agreed on the identified twenty-one values which were the important characteristics to be taught to the young people studying agriculture in high school, of which responsibility, honesty, courtesy, and respect were perceived as the most important values. The author also pointed to the fact that teachers' influence on the moral development of students is also important as well.…”
Section: Introductionmentioning
confidence: 67%
“…In agricultural education, however, few studies have been conducted to identify such attributes and indicators. Lockaby and Vaughn (1999) found that agricultural education teachers "strongly agreed" that perseverance was a value that should be taught. They further found that teachers who exhibited higher levels of persistence than teachers with lower levels, were more likely to teach perseverance to their students.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Given that respondents overall had indicated high levels of perseverance, Lockaby and Vaughn's (1999) recommendation is well placed that agricultural education teachers should teach and help students understand the importance of perseverance.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%